Determination of Potential Tidal Power Sites at East Malaysia - Samo, K. A.; Samo, I. A.; Siyal, Z. A.; Rigit, A. R. H. (Engineering, Technology & Applied Science Research, 2020)
Tidal range energy is one of the most predictable and reliable sources of renewable energy. This study’s main aim is to determine potential sites for tidal range power in East Malaysia, by analyzing tidal range distributions and resources and the feasibility of constructing barrages. Investigation was conducted in 34 sites, estimating their potential energy outputs and studying their areas for constructing barrages. Only 18 sites were marked as appropriate for constructing a tidal range energy extraction barrage. The highest potential power was found in Tanjung Manis, and its maximum capacity was calculated as 50.7kW. The second highest potential of tidal power extraction was found in Kuching Barrage at Pending, where an energy harvester could produce electric power up to 33.1kW.